{332}<113> mechanical detwinning as a deformation mechanism in the β-metastable Ti-15Mo alloy during cyclic loading. (15th July 2023) - Lilensten, Lola; Sun, Fan; Hocini, Azziz; Dirras, Guy; Vermaut, Philippe; Prima, Frédéric
Abstract: The cyclic shear study of the Ti-15Mo (wt.%) alloy, with twinning induced plasticity deformation mechanism, shows that whereas conventional {332}<113> twinning is obtained during forward loading, room temperature backward loading in Bauschinger tests are able to cause twins reversion, suggesting that detwinning can act as a proper deformation mechanism. After reversion, the mechanical twins leave behind residual bands with low misorientation (∼2°) in the matrix, and secondary twins. When the backward deformation is continued, new twins of different {332}<113> systems favorable to backward stress are then produced in the microstructure. The formation of the various deformation products is rationalized by trace analysis and calculation of the resolved shear stress on the considered twinning systems. Graphical abstract: Image, graphical abstract